A randomized controlled trial comparing labor induction at 40 versus 41 weeks in low-risk post-date pregnant women - Soni, Anjali; Khurana, Divya; Sharma, Chanderdeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To determine effect of expectant management till 41 weeks versus labor induction (IOL) at 40 weeks, on spontaneous labor onset (SOL), in low-risk post-date (>40 weeks) women. Methods: A randomized controlled trial was conducted among low-risk post-date women. At enrolment two hundred women were randomized (group 1; IOL at 40 weeks versus group 2; expectant management till 41 weeks). Demographic and clinical data were collected at enrolment and delivery. Results: Three-fourth of women (76%) in group 2 had SOL. Additionally, duration of labor (minutes) [median±IQR; 380 (325-417) versus 410 (380-482), p<0.001], delivery within 12 hours (n; 87 versus 45, p<0.001) and within 12-24 hours of admission (n; 1 versus 42, p<0.001) was statistically significantly better in group 2. There was no statistically significant difference regarding mode of delivery (n) [vaginal delivery; 87 vs. 88, or cesarean section (CS); 13 versus 12, p=0.887] and indications of CS (fetal distress; 12 versus 12, and failure of induction of labor 1 versus nil, p=1.000) and maternal and fetal/neonatal outcomes. With an absolute risk of 21% of SOL, five women should be offered expectant management till 41 weeks for one woman to have SOL. Conclusions: In low- and middle-income countries, low-risk post-date pregnant women should be offered expectant management of pregnancy till 41 weeks awaiting spontaneous labor (76%), with maternal and fetal/neonatal outcomes comparable to routine IOL at 40 weeks.